Tramadol versus placebo for labor analgesia in low risk women: a randomized controlled trial - Raheja, Aastha; Agarwal, Krishna; Pachori, Rini; Gandhi, Gauri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In low- and middle-income countries epidural analgesia is generally not available and practically no form of labor analgesia is given to the majority of the parturient. The purpose of study was to evaluate the safety and efficacy of tramadol as a labor analgesic during first stage of labor. Methods: Pregnant women admitted in the labor room satisfying the eligibility criteria were randomized to receive intramuscular injection of either 100 mg tramadol or 2 ml distilled water. Visual analogue score (VAS) was assessed at the beginning and every hour till 4 hours. Pain satisfaction, duration of second stage of labor, fetal heart rate, mode of delivery, and any maternal side effects of the study drug were recorded. Neonatal evaluation using Apgar score at 1 and 5 minutes was done. For statistical analysis Student t-test, Chi Square test and Fisher’s exact test were used. Results: Total of 86 women were included in the study. The VAS scores were significantly lower in the tramadol group at 1, 2 and 3 hours after the administration. Pain relief satisfaction was significantly higher in the tramadol group. Rate of cervical dilatation, duration of the second and the third stage, need for instrumental delivery or lower segment caesarean section, rate of fetal distress and Apgar score at one and five minutes were comparable in both the groups. Nausea was significantly higher in tramadol group. Conclusions: Tramadol is a safe and efficacious drug which is inexpensive, easily available and easy to administer with few minor side effects. It can be used as a labour analgesic as an alternative to epidural analgesia in settings where epidural analgesia is not available. Trial registration: Clinicaltrials.gov PRS registration number: NCT02999594.